1974
DOI: 10.1029/ja079i001p00215
|View full text |Cite
|
Sign up to set email alerts
|

Empirical model of global thermospheric temperature and composition based on data from the Ogo 6 quadrupole mass spectrometer

Abstract: An empirical global model for magnetically quiet conditions has been derived from longitudinally averaged N2, O, and He densities by means of an expansion in spherical harmonics. The data were obtained by the Ogo 6 neutral mass spectrometer and cover the altitude range 400–600 km for the period June 27, 1969, to May 13, 1971. The accuracy of the analytical description is of the order of the experimental error for He and O and about 3 times the experimental error for N2 and thus provides a reasonable overall re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(77 citation statements)
references
References 14 publications
5
72
0
Order By: Relevance
“…Global properties in the distribution of composition and temperature, inferred from these measurements, were reported by Reber et al (1971), Taeusch et al (1971), , Carignan and Reber (1971), Hedin et al ( , 1973aHedin et al ( , 1973b), .…”
Section: Empirical Modelmentioning
confidence: 87%
See 2 more Smart Citations
“…Global properties in the distribution of composition and temperature, inferred from these measurements, were reported by Reber et al (1971), Taeusch et al (1971), , Carignan and Reber (1971), Hedin et al ( , 1973aHedin et al ( , 1973b), .…”
Section: Empirical Modelmentioning
confidence: 87%
“…Global characteristics in the diurnal components of OGO-6 neutral mass spectrometer measurements (Carignan and Pinkus, 1968) near 450 km, which have been described empirically in analytic form (Hedin et al 1973b), are discussed qualitatively as well as quantitatively on the basis of a theoretical model ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were observed by Reber and Hedin (1974) by analyzing two years of neutral density measurements from j Ogo 6e The molecular nitrogen concentration near 450 km was found to increase, the helium density to decrease, and the atomic oxygen concentration to remain fairly stable in the region of"heating• These results appeared consistently during magnetically quiet periods, suggesting that the heating was a permanent feature of the neutral thermosphere. Corotation of this heat source with the geomagnetic ,pole indicated that some type of geomagnetic control was being exerted although no correlation with the cusp region could be found.…”
mentioning
confidence: 86%
“…"., over small regions of the thermosphere (Hedin and Reber, 1972;Reber and Hedin, 1974;Taeusch and Hinton, 1975;Nisbet and Glenar, 1977;Nisbet et al, 1978). Ina ; geographic coordinate system, these energy sources produce large longitude effects.…”
Section: 'mentioning
confidence: 99%